ESG DISCLOSURE, GREEN INTELLECTUAL CAPITAL, AND FIRM VALUE: THE MODERATING ROLE OF ENVIRONMENTAL RISK - Dira Dwi Rahmani; Christina Dwi Astuti (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study aims to analyze the effect of Environmental, Social, and Governance (ESG) Disclosure and Green Intellectual Capital (GIC) on Firm Value, with Environmental Risk as a moderating variable.METHODOLOGY - This study employs a quantitative research design with a moderating analysis approach. The data utilized consists of secondary panel data (longitudinal) gathered from the annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2025. Purposive sampling balanced total of 60 observations. Data analysis was performed using EViews 9.0 through the Fixed Effect Model (FEM) with a Cross-Section Weight approach to address heteroscedasticity.FINDINGS - The empirical results indicate that, to some extent, neither ESG Disclosure (p = 0.25845) nor Green Intellectual Capital (p = 0.1136) has a positive or significant direct effect on Firm Value in the Indonesian capital market. Furthermore, Environmental Risk does not moderate the relationship between ESG Disclosure and Firm Value (p = 0.46445), suggesting that market participants still perceive ESG reporting merely as regulatory compliance rather than a risk-mitigation strategy. However, a crucial finding reveals that Environmental Risk significantly strengthens the positive effect of Green Intellectual Capital on Firm Value (p = 0.0207, with an interaction coefficient of 0.201993).